A new forecasting method for failure time of creep landslide based on nonlinear creep behavior and new pre-warning criterion - Zhang, Shuo; Jiang, Tong; Pei, Xiangjun; Huang, Runqiu; Xu, Qiang; Xie, Yushan; Pan, Xuwei; Zhi, Longxiao (Frontiers in Earth Science, 2022)
The forecast of failure time of unstable slope and the definition of early warning threshold are very important for preventing landslide disaster and reducing its losses. Based on the monitoring curve of unstable slope deformation varying with time, the mathematical models are used to accurately describe the nonlinear creep behavior in the initial creep stage and the unstable creep stage of unstable slope and a forecasting method for creep landslide is proposed. In addition, this study examines an improved tangential angle criterion obtained by a new forecasting method. The results show that the initial creep stage of unstable slope can not be neglected for forecasting the failure time. The initial creep velocity v0 and the viscoelastic hysteresis coefficient of the slope are determined at initial creep stage, which together control the creep process of the unstable slope. Moreover, in the secondary creep stage, there is an inverse relationship between the velocity and the critical tangential angle. According to the average velocity of the secondary creep stage, the early warning criterion of the landslide tangential angle is proposed. Combined with the forecast parameters of the unstable slope, comparative analysis of the critical tangential angle warning criterion and an improved tangential angle criterion, the early warning and forecasting system of landslide with creep characteristic is established. This system is applied to the early warning and forecasting analysis of reported soil and rock landslides cases with creep characteristics. The forecasting effect and applicability of the new method are studied in order to make it a better supplement to the early warning strategy of landslide.